2016
DOI: 10.1037/fam0000219
|View full text |Cite
|
Sign up to set email alerts
|

The effect of daily challenges in children with autism on parents’ couple problem-solving interactions.

Abstract: The vulnerability-stress-adaptation model guided this examination of the impact of daily fluctuations in the symptoms and co-occurring behavior problems of children with autism spectrum disorder (ASD) on parents’ couple problem-solving interactions in natural settings and as these interactions spontaneously occur. A 14-day daily diary was completed by mothers and fathers in 176 families who had a child with ASD. On each day of the diary, parents separately reported on the child with ASD's daily level of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…Despite the previous evidence of effects of comorbid conditions on families of children with ASD (Hartley et al, ; Lecavalier et al, ; and Peacock et al, ), the present authors found inconsistent or little evidence of this. In this study, family mental health counselling, respite services, work‐life changes and weekly hours of care were not significantly impacted by the presence of comorbid conditions.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Despite the previous evidence of effects of comorbid conditions on families of children with ASD (Hartley et al, ; Lecavalier et al, ; and Peacock et al, ), the present authors found inconsistent or little evidence of this. In this study, family mental health counselling, respite services, work‐life changes and weekly hours of care were not significantly impacted by the presence of comorbid conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…Some research has found similarities in mothers’ and fathers’ experiences of raising a child with ASD (Hartley & Schultz, ), including similar levels of optimism and coping strategies (Willis et al, ). Mothers and fathers can also show great resilience to the daily severity of autism symptoms by not letting these experiences affect marital cooperation (Hartley, Papp, Blumenstock, & Floyd, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the couple relationship has been found to be a predictor of parental well‐being [Hartley, Papp, Blumenstock, Floyd, & Goetz, ; Kersh, Hedvat, Hauser‐Cram, & Warfield, ; Norlin & Broberg, ], coping [Siman‐Tov & Kaniel, ], and burden [Hartley, Barker, Seltzer, Greenberg, & Floyd, ] in families of individuals with ASD and DD.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current literature, it is unclear whether parents’ and teachers’ general predisposition to communicate is related to the extent that they display the core elements of problem solving. Within families, couples’ ability to problem solve relates to their partners’ behaviors (Hartley, Papp, Blumenstock, Floyd, & Goetz, ). From the current research, we do not know whether teachers’ problem solving behaviors may impact parents’ willingness to problem solve and vice versa.…”
Section: Introductionmentioning
confidence: 99%